OTUB1 Recruits Tumor Infiltrating Lymphocytes and Is a Prognostic Marker in Digestive Cancers - Zhang, Wenhao; Qiu, Wenlong (Frontiers in Molecular Biosciences, 2020)
Background The deubiquitinating enzyme (DUB) OTUB1 can regulate the process of ubiquitination, but the influence of OTUB1 on immunity, apoptosis, autophagy, and the prognosis of digestive cancers requires further exploration. Methods OTUB1 expression was analyzed with the Oncomine and TIMER database. Kaplan-Meier plotter was used to calculate the association between OTUB1 and clinical prognosis. The regulation of OTUB1 on cancer immunocyte infiltration was determined by the TIMER database. The interaction between OTUB1 and immune genes, gene expression profiling (GEP), key genes of apoptosis and autophagy were analyzed via GEPIA. Protein-protein interaction (PPI), gene expression profiling (GEP), and functional pathway enrichment were also performed with the STRING and Pathway Common databases, respectively. Results High OTUB1 expression was found in CHOL, LIHC, READ, ESCA, and COAD, which was significantly associated with the poorer OS of LIHC (HR = 2.07, 95% CI = 1.30–3.30, P = 0.002), with modifications by sex, stage, grade, and mutant burden. OTUB1 can promote the recruitment of B cells, CD8 + T cells, macrophages in ESCA, B cells, and neutrophils in LIHC. We determined a significant interaction between OTUB1 and USP8, RNF128, LRIG1, UBB, UBC, STAM2, RNF41, EGFR, RPS27A, and HGS by PPI. This functional pathway indicates the regulatory role of OTUB1on immune, apoptosis, and autophagy through its interaction with TP53 and ATG. Conclusions OTUB1 performed as a molecular indicator of poor prognosis in digestive cancers, regulated the infiltration of tumor immunocytes, and exerted a significant influence on apoptosis and autophagy. OTUB1 is a potential antitumor target for digestive tumors.